ANALISIS MATERIAL SERAT ALAM TEBU SEBAGAI BAHAN PEREDAM SUARA - Billy Cessar Bimara; Aulia Rahma Azizah; Tri Anita Wulansari; Upik Nurbaiti; Fianti Fianti (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2021)
Abstract Material Sugarcane natural fiber material can be used as a sound absorber material. In measuring the value of the sound absorption coefficient of the cane natural fiber silencer using the sound level meter application on the smartphone to measure the intensity of sound (dB) and the frequency generator application connected to the speaker as a sound source (Hz). The test uses an acoustic box as a miniature room that will be tested for its sound absorption coefficient values coated with sugarcane natural fibers. The purpose of this study is to find out the influence of sugarcane fibers in reducing noise and to find out the effect of frequency variations on the value of the sound absorption coefficient. Measurement of the noise level of the sugarcane natural fiber material on the acoustic wall produces different sound absorption coefficient values based on variations in the frequency of the sound source. The greater the frequency value, the higher the absorption coefficient value. Frequency variations used include 500 Hz, 1000 Hz, 1500 Hz, 2000 Hz, 2500 Hz, and 3000 Hz. The value of the sound absorption coefficient drops at a frequency of 1000 Hz but there is a re-increase at frequencies above 1500 Hz. The smallest sound absorption coefficient is obtained at the time of frequency 1500 Hz with a value of = 0.01047 and the largest at the time of frequency 3000 Hz with a value of = 0.10139. The coefficient value is too small, so it is not effective in muffling the sound.